A critical review of the treatment of dominant firms in competition law : a comparative study - Munyai, Phumudzo S. (University of South Africa, 2016)
In South Africa compliance with competition law has become a major concern for firms that achieve and maintain certain levels of success and growth in the market, as their actions are often a source of complaints and litigation by rivals and competition authorities. With substantial financial penalties often levied against them for a variety of conduct deemed to constitute an abuse of their market position, dominant firms must constantly be aware of the likely impact of their business strategies and actions on both rivals and consumers. What were once thought to be normal and economically sound business practices and decisions, such as cutting prices to attract customers, have now acquired new meanings, with devastating consequences for dominant firms. So, are dominant firms under attack from competition law? In this study I aim to determine this. I track the historical development of competition law in three jurisdictions: South Africa, America, and the EU, with the aim of identifying traces, if any, of hostility towards dominant firms in the origins of competition law. I further investigate whether the formulation and enforcement of certain aspects of existing abuse of dominance provisions manifest as hostility towards dominant firms. While acknowledging the important role that competition law enforcement plays in promoting competition and enhancing consumer welfare, I conclude that significant unjustified economic and legal prejudice is suffered by dominant firms as a result of the way in which certain abuse of dominance provisions have been formulated and applied. I also offer appropriate recommendations.
Keywords: Abuse of dominance; Anti-monopoly; Anticompetitive effects; Anticompetitive harm; Antitrust law; Causation; Competencia; Competition Appeal Court; Competition Commission; Competition Tribunal; Competition law; Consumer harm; Consumer welfare; Counterfactual; Dominant firms; Exclusionary conduct; Hostility; Monopoly; Super-dominant; Unilateral conduct

The Interface Between Competition Law and Intellectual Property Law in Kenya - Jerobon, Rotich Caroline (University of Nairobi, 2016)
The interaction between competition law and intellectual property law has often attracted divergent views from scholars and practitioners of each respective sphere of law. Whereas some argue that the two are in conflict with each other and cannot be reconciled. The aforementioned tension between competition law and intellectual property law has been traced to the objectives of each. On the one hand, intellectual property rights confer upon their owners an exclusive right to behave in a particular way while on the other hand competition law strives to keep markets open. Other scholars have argued that, in real sense and practice, the two are actually not in conflict but rather that they complement each other. The question then becomes, is there really an irreconcilable difference between the two areas of law? This paper seeks to establish how the two aspects of law interact and seeks to propose that there be created a balance to alleviate the perceived conflict between the two. This paper will identify the areas in which the balance can be struck. It will also seek to establish how the Kenyan legislative framework as well as the courts has dealt with the conflict. It will proceed from understanding the goals and objective of both intellectual property law and competition law. This will provide the backdrop against which the alleged conflict originates from. A comparative study with other developed jurisdictions will be undertaken so as to advise on the route that should be taken by Kenya on the interface and a conclusion drawn on how the two areas relate and recommendations drawn from the issues identified in the study made.
Keywords: Competencia; Competition law; Intellectual property

The Regulation of Promotional Competitions in South Africa - Strachan, Daniel Petrus (University of Pretoria, 2016)
Promotional competitions are competitions in which prizes are awarded by lot or chance in order to promote goods or services. Due to the chance element, these competitions are often categorised as lotteries or gambling. Initially, South African legislation did not make provision for the running of promotional competitions, but this situation changed when the Lotteries Act, 1997 came into force. Currently, promotional competitions are regulated by the Consumer Protection Act, 2008 (CPA). This thesis examines the regulation of promotional competitions in South Africa. It commences with a background discussion, which touches on the relevant terminology and some sociological aspects. It then considers the consequences of gambling and the need for and nature of regulation, and deals with the marketing and consumer protection contexts. This is followed by a brief overview of the global and South African history of gambling, lotteries and promotional competitions, which includes a discussion of South African case law. Foreign law relating to promotional competitions in New Zealand and Great Britain is explored in order to compare this to the South African position. This is followed by an examination of the current regulation of promotional competitions in South Africa, including a discussion regarding the interplay between the CPA and the Lotteries Act and a detailed analysis of the CPA’s provisions. The self-regulation of promotional competitions is discussed as well. The concluding chapter of this thesis contains recommended solutions for the problems identified in the analysis of the relevant legislation.
URI: https://repository.up.ac.za/handle/2263/56056
Keywords: Competencia; Competition law; Concurrence (droit); Consumer law; Droit de la consommation